2022
DOI: 10.1080/10717544.2022.2126559
|View full text |Cite
|
Sign up to set email alerts
|

Increased brain uptake of pterostilbene loaded folate modified micellar delivery system

Abstract: Effective chemotherapy for clinical treatment of brain diseases is still lacking due to the poor penetration of the blood-brain barrier (BBB). The aim of this study was to construct a folate modified pterostilbene (Pt) loaded polymeric micellar delivery system (F-Pt/M) with mPEG-PCL as carrier material to aim at penetrating the BBB for brain tissue targeting via receptor-mediated endocytosis. In this study, F-Pt/M was prepared using thin-film hydration method and then optimized by response surface methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…[34,35] After incubation for 6 h, the uptake of FAP-CAR-CM@PLGA-C6 NPs by CAFs was higher than that of CM@PLGA-C6 NPs, probably owing to the specific binding of FAP scFV on FAP-CAR-CM to FAP expressed by CAFs. [36] Confocal laser scanning microscope (CLSM) further visualized the uptake of different NPs by CAFs for 6 h, and the results were consistent with the flow-cytometric quantification results (Figure 2C; Figure S6A, Supporting Information). After incubating CM@PLGA-C6 NPs and FAP-CAR-CM@PLGA-C6 NPs with CAFs for 24 h, the uptake behavior of CAFs for different nanoparticles was consistent with that at 6 h (Figure S7, Supporting Information).…”
Section: Clearance Of Cafs By Fap-car-cm@plga-ab Npssupporting
confidence: 79%
“…[34,35] After incubation for 6 h, the uptake of FAP-CAR-CM@PLGA-C6 NPs by CAFs was higher than that of CM@PLGA-C6 NPs, probably owing to the specific binding of FAP scFV on FAP-CAR-CM to FAP expressed by CAFs. [36] Confocal laser scanning microscope (CLSM) further visualized the uptake of different NPs by CAFs for 6 h, and the results were consistent with the flow-cytometric quantification results (Figure 2C; Figure S6A, Supporting Information). After incubating CM@PLGA-C6 NPs and FAP-CAR-CM@PLGA-C6 NPs with CAFs for 24 h, the uptake behavior of CAFs for different nanoparticles was consistent with that at 6 h (Figure S7, Supporting Information).…”
Section: Clearance Of Cafs By Fap-car-cm@plga-ab Npssupporting
confidence: 79%
“…In general, attaching targeting ligands that can specifically target membrane receptors or transporters has been developed to overcome the BBB transport limitation . For instance, a previous report from Wang and coworkers revealed that BBB penetration of folic acid (FA)-modified pterostilbene-loaded polymeric micellar particles, originating from poly­(ethylene glycol- b -caprolactone), was about 4-fold higher than free pterostilbene . The reported study clearly showed FA conjugation on polymeric brushes was a critical parameter for improving brain accumulation through receptor-mediated endocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…22 For instance, a previous report from Wang and coworkers revealed that BBB penetration of folic acid (FA)-modified pterostilbene-loaded polymeric micellar particles, originating from poly(ethylene glycol-b-caprolactone), was about 4-fold higher than free pterostilbene. 61 The reported study clearly showed FA conjugation on polymeric brushes was a critical parameter for improving brain accumulation through receptor-mediated endocytosis. Therefore, the surface modification of brush polymer with FA was expected to be effective and potentially have a great impact on the association and transport of our brush system across hCMEC/D3 cells.…”
Section: Effect Of Size and Shape Of Nonfunctionalized Polymers On It...mentioning
confidence: 89%
“…With free PTE ethanol solution as control, in vitro release properties of PTE from PTE-MMs were analyzed using a previously reported dialysis method. , Briefly, 1 mL of the prepared PTE-MMs was placed in a dialysis bag, which was then shaken in PBS solutions at pH 7.25 (containing 0.5% Tween 80). Samples were taken between 0 and 36 h and replaced with the same volume of PBS.…”
Section: Methodsmentioning
confidence: 99%